Constructions, reconstructions and deconstructions of 'family' amongst people who live apart together (LATs). (19th September 2016) - Stoilova, Mariya; Roseneil, Sasha; Carter, Julia; Duncan, Simon; Phillips, Miranda
Abstract: This article explores how people who live apart from their partners in Britain describe and understand 'family'. It investigates whether, and how far, non‐cohabiting partners, friends, 'blood' and legal ties are seen as 'family', and how practices of care and support, and feelings of closeness are related to these constructions. It suggests that people in LAT relationships creatively draw and re‐draw the boundaries of family belonging in ways that involve emotionally subjective understandings of family life, and that also refer to normative constructions of what 'family' ought to be, as well as to practical recognitions of lived family 'realities'. This often involves handling uncertainties about what constitutes 'family'.